The Role of Islam in the Preservation and Transformation of Sasak Traditions: An Ethnographic Study of the Merariq Tradition among Minors - Ahmad Khaerul Kholidi; Irwan; Abdul Azis (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
Early marriage remains a pressing social issue in Indonesia, particularly in Lombok, where the Sasak community practices merariq (elopement). While deeply rooted in local culture, merariq often intersects with underage marriage, raising concerns about child protection, education, and health. Islam plays a pivotal role in addressing this challenge, not only as a source of religious doctrine but also as a moral and ethical framework guiding family life and social responsibility. This study explores how Islamic values interact with Sasak traditions, functioning both as a preservative force and as an agent of transformation. The research employs a qualitative ethnographic approach, combining fieldwork in Banyu Urip Village, Central Lombok, with policy brief analysis. Data were collected through participant observation, interviews with community leaders, religious figures, parents, and youth, as well as document review. Findings reveal that while merariq embodies symbolic meanings of freedom, honor, and cultural identity, its contemporary practice often perpetuates early marriage due to economic hardship, social pressure, and limited educational access. At the same time, Islamic teachings emphasize maturity, responsibility, and protection of children’s rights, creating tension between tradition, religion, and state law. This study concludes that Islam provides a normative foundation to reinterpret merariq in ways that discourage underage marriage, offering pathways for cultural integration that respect local wisdom while safeguarding children. The results contribute to broader discussions on how religion can mediate tradition and modern legal frameworks, informing culturally sensitive policies for child protection in Indonesia.